Makna Gerak Tari Kombuik di Desa Gunung Sahilan Kecamatan Gunung Sahilan Kampar Kiri Kabupaten Kampar - Uswatun Hasanah; Yahyar Erawati (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of this research is to ascertain the significance of the Kombuik Dance Movement in Gunung Sahilan Village, Kampar Kiri Regency's Gunung Sahilan District. The study comes to the conclusion that each of the nine movement kinds has a distinct significance. In addition to the message conveyed by this movement, the dance's main goal is to express gratitude to Allah SWT, who has provided the local community with an abundance of sustenance through the rice harvest. It also aims to demonstrate to the larger public how the local community expresses gratitude for the gifts and sustenance they have received. This dance is often done in the village of Gunung Sahilan's major festivals. For instance, the Ka Gun holiday is usually observed on the second of Syawal, which is Eid al-Fitr..